Gestão do conhecimento em aceleradoras de startups: estudo de processos, práticas e ferramentas de TI utilizadas por empresas no Brasil - Aihara, Celia Hatsumi (2019)
The challenges imposed on companies to stay in an increasingly competitive market make them seek to develop greater agility to respond to the contemporary business environment, notably by introducing new products, services and processes. Among the forms found by companies to do so is the use of innovation to keep evolving. However, innovation and its management within in the company’s own boundaries are somewhat limited. In this way, a solution found by companies in recent years turns to startups. Although, startups often have good new business ideas, they cannot make them viable, so they seek for startup accelerators. Therefore, startup accelerators have become an important initiative for companies, since they can help to make possible the introduction of innovation in society, mainly through the knowledge developed by startups. In addition, another strategic resource has been considered that has been emphasizing over the last years for the evolution of companies: knowledge management in the organization. Considering the context observed, the general objective of this dissertation research was to identify and characterize the main processes, practices and Information Technology’s (IT) tools used in knowledge management by startup accelerators operating in Brazil. The methodology used considered an exploratory-qualitative approach, using the multiple case study research method. The research instruments adopted were interviews with semi-structured script and documentary analysis of public records. As a main results were identified the use of multiple processes, practices and IT tools, yet so unstructured for nearly all analyzed accelerators, except for one in which there was the use of structured knowledge management. It was found practices and IT tools focused on knowledge management more focused on the 'identification/mapping' and 'distribution/sharing' phases of the knowledge management process. Among the highlighted practices are the knowledge mapping, knowledge maps, places and events dedicated to the socialization of knowledge, mentoring, classroom training and enterprise portal/departments. As for IT tools, the most commonly used are WhatsApp or similar groups, meetings and virtual conferences, mobile phone, other telephony media such as Skype, extranet, social networks and cloud computing. As a conclusion, it was possible to verify the importance of the use of knowledge management by startup accelerators surveyed, according to their representatives. This is because it was realized, according to the company’s representatives that the knowledge management adequately implemented at the startup accelerator can bring benefits and advantages for them and the associated startups, in this way making possible to introduce faster the innovations in the society.